DEVELOPMENT OF TECHNOLOGY-BASED LEARNING MEDIA USING ADOBE PREMIERE PRO ON ANCIENT RELICS OF SRIWIJAYA KINGDOM ON SIGUNTANG HILL TO MITIGATE ONLINE LEARNING PROBLEMS DURING COVID-19 PANDEMIC - Bunga Wulandari; Syarifuddin Syarifuddin (Akademika : Jurnal Teknologi Pendidikan, 2022)
This study uses a Research and Development approach applied towards teaching materials regarding the ancient relics of the long-gone Sriwijaya Kingdom found on Siguntang Hill. The target audience of this study is students of grade X (ten) of Senior High School 15 Palembang. The Research and Development method used in this study is from Hannafin and Peck, while the validators for the resulting materials are from experts in their respective fields related to this study, that is: media, materials and learning design experts respectively. The purpose of this study is to see the effectiveness of the products produced during online learning. This effectiveness is proven by a 39.37% increase in the students’ learning outcomes with an N-gain of 0.74 after utilizing Adobe Premiere Pro in the online learning process. This means that the utilization of Adobe Premiere Pro in the context of technology-based learning media is effective and thus valid. learning media development, history education, Adobe Premiere Pro